2004
DOI: 10.1111/j.1461-9555.2004.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Steinernema species in cabbage fields and the effect of inoculated S. feltiae on Delia radicum and its parasitoids

Abstract: 1 Seven organically grown cabbage fields were surveyed for entomopathogenic nematodes in the autumn by baiting. Nematodes were obtained from three fields with bait larvae infection ranging from 1.3-4.0%. 2 Inoculation of Steinernema feltiae (Rhabditida: Steinernematidae) in the spring increased bait larvae infection to 16.0-32.0%. 3 Four different species were found (Steinernema affine, Steinernema bicornutum, S. feltiae and Steinernema C1). 4 The number of Delia radicum (L.) (Diptera: Anthomyiidae) puparia wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…The occurrence of entomopathogenic nematodes has been studied in many countries (Hominick, 2002) and the presence of the species S. feltiae and S. affine in the present cropping system is in accordance with observations made in agricultural soils in other countries in northern Europe (Blackshaw, 1988;Husberg et al, 1988;Ehlers et al, 1991;Griffin et al, 1991;Boag et al, 1992;Hominick et al, 1995;Sturhan, 1996;Nielsen & Philipsen, 2004a). The level of naturally occurring nematodes was generally low (<20%) and could be a result of the soil type, which resulted in very hard and compact soil under dry conditions as well as a tendency to plasticity under wet conditions.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The occurrence of entomopathogenic nematodes has been studied in many countries (Hominick, 2002) and the presence of the species S. feltiae and S. affine in the present cropping system is in accordance with observations made in agricultural soils in other countries in northern Europe (Blackshaw, 1988;Husberg et al, 1988;Ehlers et al, 1991;Griffin et al, 1991;Boag et al, 1992;Hominick et al, 1995;Sturhan, 1996;Nielsen & Philipsen, 2004a). The level of naturally occurring nematodes was generally low (<20%) and could be a result of the soil type, which resulted in very hard and compact soil under dry conditions as well as a tendency to plasticity under wet conditions.…”
Section: Discussionsupporting
confidence: 75%
“…In agricultural soils in northern Europe, which is the focus of this study, the most common species appeared to be Steinernema affine (Bovien) and S. feltiae (Filipjev) (Blackshaw, 1988;Husberg et al, 1988;Hominick & Briscoe, 1990a;Ehlers et al, 1991;Griffin et al, 1991;Boag et al, 1992;Hominick et al, 1995;Sturhan, 1996;Nielsen & Philipsen, 2004a).…”
mentioning
confidence: 95%
“…Our experiments were not designed for the purpose of studying these multitrophic interactions but the results with S. carpocapsae and H. bacteriophora (Figure 4) indicated that reductions in recovery will be lower when a high proportion of the pollen beetles are parasitised by wasps. A few earlier studies have observed that parasitoid wasps can be negatively affected by entomopathogenic nematodes (Kaya and Hotchkin, 1981;Battisti, 1994;Nielsen and Philipsen, 2004b) and also the present study gave significant reductions in the hatching of parasitoids in most cases. The timing of the attack of the insect parasite is probably important for its success and an example of this was given by Reader and Jones (1990) who studied the competition between two parasites of the cabbage root fly, Delia radicum.…”
Section: Discussionsupporting
confidence: 55%
“…The said organism was first found in 1937, while its usefulness in biological plant protection was discovered a few years ago (Willmott et al, 2002). This species often appears in soils where plants of the family Brassicaceae are cultivated (Nielsen and Philipsen, 2004). Cabbage was cultivated also in the field located not far from Staro selo near Kobarid, where we confirmed the presence of the said nematodes.…”
Section: Steinernema Affine Boviensupporting
confidence: 61%
“…Cabbage was cultivated also in the field located not far from Staro selo near Kobarid, where we confirmed the presence of the said nematodes. Steinernema affine is known to be exceptionally efficient biological agent for suppressing cabbage root fly (Delia radicum [L.]) (Willmott et al, 2002;Nielsen and Philipsen, 2004). Cabbage is in Slovenia the most widely cultivated vegetable (24.1 % of all fields or 871 ha) (the Statistical Office of the Republic of Slovenia, 2005), which makes the said plant from the family Brassicaceae even more useful.…”
Section: Steinernema Affine Bovienmentioning
confidence: 99%